Pengaruh Penerapan Model Kooperatif Tipe Teams Games Tournament Dengan Pendekatan Saintifik Terhadap Hasil Belajar Matematika Siswa Kelas VII MTs Fie Sabilil Muttaqien Tempurejo Desa Tempuran - Dwi Nadia Putri; Budi Sasomo; Pratiwi Novitasari (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
The learning model is very important and has many benefits in the teaching and learning process, with the help of the learning model educators can also motivate students to be actively involved in learning and totality so as to affect student learning outcomes. Through a cooperative learning model of the team games tournament type with a scientific approach, it is hoped that it will be able to improve student learning outcomes. This study aims to determine the effect of the application of the cooperative learning model of the team games tournament type with a scientific approach on the mathematics learning outcomes of grade VII MTs Fie Sabilil Muttaqien Tempurejo students for the 2023/2024 school year. The method in this study is a quantitative Quasi Experiment with a posttets only control group design research design. This study consists of independent variables and bound variables. The independent variable is the learning model used, namely a cooperative model of the team games tournament type with a scientific approach while the bound variable is the learning outcome. The subject of this study is grade VII students of MTs FSM Tempurejo with 23 students in the experimental class and 23 students in the control class. Data collection is carried out by means of a posttest given at the end of learning which is used to determine student learning outcomes. The results showed a significant difference with the value of t calculated = 2.134 and t table = 1.080 with a significance level of 0.05. The average score of students after being taught using a cooperative model of teamgames tournament type with a scientific approach was 80.04, while the average score of students with a direct learning model was 68.65. Thus, the application of a cooperative learning model of the team games tournament type with a scientific approach is more effective on the mathematics learning outcomes of grade VII MTs students Fie Sabilil Muttaqien Tempurejo for the 2023/2024 school year.